The geology and the structure of the area in the vicinity of Magnet Heights, Eastern Transvaal, with special reference to the Magnet Iron Ore - Molyneux, Thomas Gordon (University of Pretoria, 2022)
Dissertation (MSc)--University of Pretoria, 1964.